Nitrate concentration within the principal aquifers in the Central Valley of Costa Rica, 1989-2005 to 2006-2015 - Mora-Alvarado, Darner A. (2017)
The study seeks to analyse the nitrate concentrations in 24 water sources within the aquifers of Barva, Colima Superior and Colima Inferior, from 1989 to 2005 and 2006 to 2015, in order to verify that these nitrate concentrations are in compliance with the maximum allowable value stipulated on the current Drinking Water Quality Regulation (50 mg/L). About 2,500 water samples were analysed from 1989 to 2015 in 24 water sources (i.e. headwaters and water wells) within the aquifers Barva, Colima Superior and Colima Inferior. The National Laboratory of Waters (Laboratorio Nacional de Aguas, LNA) provided all the nitrate dataset by means of the Drinking Water Control and Vigilance Programme. The 24 water sources presented drinking water quality regarding the nitrate values. The nitrate average was lower than 25 mg/L for the water sources, except for the headwater La Libertad and the well Belén 3. Colima Superior was the most vulnerable aquifer, and La Libertad (Colima Superior aquifer) was the sampling point with higher risk of nitrate pollution showing 26.3 mg/L, for 1989-2005, to 30.3 mg/L, for 2006-2015. Frequent monitoring of the 24 water sources within the aquifers Barva, Colima Superior and Colima Inferior should be done for establishing the baseline.